Long-term prevalence follow-up (1967–2022) of HTLV-2 among vulnerable indigenous populations in the Amazon region of Brazil - Ishak, Ricardo; de Oliveira Guimarães Ishak, Marluísa; Abreu, Isabella Nogueira; Machado, Luiz Fernando Almeida; Lima, Sandra Souza; Queiroz, Maria Alice Freitas; Cayres-Vallinoto, Izaura Maria; Guerreiro, João Farias; Vallinoto, Antonio Carlos Rosário (Frontiers in Microbiology, 2023)
Human T-lymphotropic virus 2 (HTLV-2) has been described for more than 30 years as an endemic infection in Brazilian indigenous populations, with its occurrence varying by age and sex, maintained mainly by sexual intercourse and mother-to-child transmission, favoring intrafamilial aggregation. The epidemiological scenario of HTLV-2 infection has been described among communities of the Amazon region of Brazil (ARB), with the number of retrospective positive blood samples increasing for more than 50 years. Five publications were selected that showed the presence of HTLV-2 in 24 of 41 communities; the prevalence of infection was described among 5,429 individuals at five points in time. Among the Kayapó villages, the prevalence rates were described according to age and sex and reached up to 41.2%. Three communities (Asurini, Araweté and Kaapor) were kept virus free for 27 to 38 years of surveillance. Low, medium and high prevalence levels of infection were defined, and two pockets of high endemicity were shown in the state of Pará, pointing to the Kikretum and Kubenkokrê Kayapó villages as the epicenter of HTLV-2 in the ARB. The prevalence rates over the years have shown a decline among the Kayapó (from 37.8% to 18.4%) and an apparent change to a higher prevalence among females, but not during the first decade of life, usually associated with transmission from mother to child. Sociocultural and behavioral aspects, as well as public health policies directed toward sexually transmitted infections, might have positively influenced the decline in HTLV-2 infections.